The possible numbers of repair can be Carried on the same light-cured Composite resin surface (In vitro study) (Mustansiria Dental Journal, 2018)
This study was done to determine the possible number of repair that can be carriedout on the same light-cured microfilled composite resin (Helioprogress, vivadent,Germany). 40 specimens were prepared, stored in deionized distilled water at 37°Cfor 24 hours and divided into 4 groups.Group 1: The repair procedure done once.Group 2: The repair procedure done twice.Group 3: The repair procedure done for three times.Group 4: The repair procedure done for four times.All the specimens stored in deionized distilled water at 37°C for 24 hours beforetesting. A universal zwick testing machine with a special designed chisel was used toevaluate the shear bond strength of the repaired composite resin. The results showedreduction in mean shear bond strength value from group 1 to group 4, furthermore asignificant difference was found between group 1 Vs group 3 and group 1 Vs group 4.